Blood pressure and social class in a Jamaican community. - Dressler, W W (1988)
A study of social factors and blood pressure was conducted in a Jamaican community among a sample of 199 persons ages 30 to 50. After controlling for obesity, age, and respondent tension (and other covariates), interaction effects of social class x sex for systolic and diastolic blood pressure were found. Blood pressure increased with increasing social class for males and decreased with increasing social class for females.